Treatment of atherosclerosis by traditional Chinese medicine: Questions and quandaries. (October 2018) - Wang, Chuan; Niimi, Manabu; Watanabe, Teruo; Wang, Yanli; Liang, Jingyan; Fan, Jianglin
Abstract: Atherosclerosis and its complications, such as myocardial infarction and stroke, are the major causes of morbidity and mortality, and development of effective therapies for both prevention and treatment of this disease is critically important. Currently, there are many drugs available for atherosclerotic disease, but the lipid-lowering drugs statins are still the first-choice for treatment of hypercholesterolemia, a major risk factor for atherosclerosis. On the other hand, traditional Chinese medicines, mainly Chinese herbal medicines (CHM), have been widely used in China and in other Asian countries for the treatment of atherosclerotic diseases. Although many CHMs have been reported to be effective for treating atherosclerotic diseases for more than two thousand years, there are still many difficulties for their use, such as lack of scientific evidence assessed by rigorous clinical trials, complicated components and unclear pharmacological mechanisms, which often hamper the widespread use of CHMs in Western countries. Due to these concerns, CHMs are usually considered as complimentary or alternative treatment for atherosclerotic diseases. In this review, we provide an overview of the pathophysiology of atherosclerosis viewed by Western and traditional Chinese medicine, summarize pros and cons on the efficacy of CHMs for atherosclerosis and discuss what is necessary for CHM use to spread to Western societies. Highlights: The first review article to address whether Chinese herb medicines can treat atherosclerosis. What is known and unknown about Chinese herb medicine for the treatment of atherosclerosis Con and pro of Chinese herb medicine for atherosclerosis compared with Western medicine.